Endothelial Activation, Acute Kidney Injury, and Cognitive Impairment in Pediatric Severe Malaria - Ouma, Benson J.; Ssenkusu, John M.; Shabani, Estela; Datta, Dibyadyuti; Opoka, Robert O.; Idro, Richard; Bangirana, Paul; Park, Gregory; Joloba, Moses L.; Kain, Kevin C.; John, Chandy C.; Conroy, Andrea L. (Critical care medicine, 2020)
Evaluate the relationship between endothelial activation, malaria complications, and long-term cognitive outcomes in severe malaria survivors.Prospectively cohort study of children with cerebral malaria, severe malarial anemia, or community children. Mulago National Referral Hospital in Kampala, Uganda.Children 18 months to 12 years old with severe malaria (cerebral malaria, n = 253 or severe malarial anemia, n = 211) or community children (n = 206) were followed for 24 months.Children underwent neurocognitive evaluation at enrollment (community children) or a week following hospital discharge (severe malaria) and 6, 12, and 24 months follow-up. Endothelial activation was assessed at admission on plasma samples (von Willebrand factor, angiopoietin-1 and angiopoietin-2, soluble intercellular adhesion molecule-1, soluble vascular cell adhesion molecule-1, soluble E-Selectin, and P-Selectin). False discovery rate was used to adjust for multiple comparisons. Severe malaria was associated with widespread endothelial activation compared with community children (p < 0.0001 for all markers). Acute kidney injury was independently associated with changes in von Willebrand factor, soluble intercellular adhesion molecule-1, soluble E-Selectin, P-Selectin, and angiopoietin-2 (p < 0.0001 for all). A log10 increase in angiopoietin-2 was associated with lower cognitive z scores across age groups (children < 5, β −0.42, 95% CI, −0.69 to −0.15, p = 0.002; children ≥ 5, β −0.39, 95% CI, −0.67 to −0.11, p = 0.007) independent of disease severity (coma, number of seizures, acute kidney injury) and sociodemographic factors. Angiopoietin-2 was associated with hemolysis (lactate dehydrogenase, total bilirubin) and inflammation (tumor necrosis factor-α, interleukin-10). In children with cerebral malaria who had a lumbar puncture performed, angiopoietin-2 was associated with blood-brain barrier dysfunction, and markers of neuroinflammation and injury in the cerebrospinal fluid (tumor necrosis factor-α, kynurenic acid, tau).These data support angiopoietin-2 as a measure of disease severity and a risk factor for long-term cognitive injury in children with severe malaria.
Keywords: child health, cognition, critical illness, kidney, malaria, vascular endothelium